?A REVIEW OF FELDSPATHIC RAW MATERIALS' INCORPORATION IN GLASS AND CERAMICS (Biological Sciences - PJSIR, 1998)
Feldspathic raw materials-feldspars and nepheline syenite are the essential ingredients of glas and ceramics compositions. In ceramics these materials exhibit valuable fluxing properties by lowering the melting point and bonding the other constituents together on solidification. The incorporation of these materials in thc glass batch add alumina to the glass and at the same time serves as a solvent for silica grains.